Making industrial Pittsburgh modern : environment, landscape, transportation, energy & planning - Muller, Edward K. (University of Pittsburgh Press, 2019)
Pittsburgh's explosive industrial and population growth between the mid-nineteenth century and the Great Depression required constant attention to city-building. Private, profit-oriented firms, often with government involvement, provided necessary transportation, energy resources, and suitable industrial and residential sites. Meeting these requirements in the region's challenging hilly topographical and riverine environment resulted in the dramatic reshaping of the natural landscape. At the same time, the Pittsburgh region's free market, private enterprise emphasis created socio-economic imbalances and badly polluted the air, water, and land. Industrial stagnation, temporarily interrupted by wars, and then followed deindustrialization inspired the formation of powerful public-private partnerships to address the region's mounting infrastructural, economic, and social problems. The sixteen essays in Making Industrial Pittsburgh Modern examine important aspects of the modernizing efforts to make Pittsburgh and Southwestern Pennsylvania a successful metropolitan region. The city-building experiences continue to influence the region's economic transformation, spatial structure, and life experience.